Development of Inquiry-Based Interactive Learning Media Assisted by the Articulate Storyline Application in Class V of State Elementary School 173393 Dolok Sanggul - Purba, Naomi Febiola; Ananda, Lala Jelita; Lubis, Wildansyah; Tamba, Robenhart; Prawijaya, Septian (Indonesian Journal of Advanced Research, 2023)
This development research aims to determine the effectiveness, validity and practicality of learning media using the Articulate Storyline application in Class V of SD Negeri 173393 Dolok Sanggul T.A 2022/2023. This type of research is Research and Development (R&D) using the ADDIE development model. The subjects in the research were fifth grade students at SD Negeri 173393 Dolok Sanggul T.A 2022/2023. The object in this research is learning media using the Articulate Storyline application. The results of validation by media experts obtained scores of 90% and 95% with very feasible criteria, then material validation by material experts obtained score percentages of 80% and 85% with suitable criteria for use, practicality validation was carried out by practicality experts, obtaining a score percentage of 100% with very good criteria. Practically, the learning outcomes test obtained an average effectiveness of 44% and 87% with effective criteria. And the N-Gain value was obtained at 0.77. So it can be concluded that inquiry-based interactive learning media assisted by the Articulate Storyline application in Class V of SD Negeri 173393 Dolok Sanggul T.A 2022/2023, is very feasible, very practical and effective for use in the learning process.